Transforming Family Planning Outlook and Practice in Egypt : A Rights-Based Approach - Rabie, Tamer; Boehmova, Zuzana; Hawkins, Loraine; Tawab, Nahla Abdel; Saher, Sally; El Shitany, Atef (World Bank, Washington, DC, 2014)
Family planning (FP) program contributed to Egypt s progress in reducing infant and maternal mortality and the total fertility and population growth rates. The Arab spring has brought to the forefront long-held aspirations, which can only be fulfilled by a clear shift to a rights-based and person-centered family planning approach and away from an imposed top-down program with targets for family size and fertility rate. The essence of a rights-based approach to FP is interacting with people as individuals with rights to control ones lives, not as a target of a particular program. The FP program also needs to determine and mitigate the factors that make it difficult for the poor, young, and marginalized groups to exercise rights to receive the services needed. The authors of this report examined the challenges facing Egypt s FP program through a human rights lens, exploring whether individuals and couples are able to exercise their rights to financial and physical access to good quality FP services. The research also investigated whether client demand for services, and the acceptability of those services, is guided by human rights aspects of service delivery, such as the rights to information, privacy, confidentiality, method choice, and the autonomy to choose the number and spacing of births. This report synthesizes the findings from three sources: (i) an analysis of legal and ethical codes and institutions for upholding reproductive rights in Egypt; (ii) a literature review of past studies and surveys in Egypt; and (iii) a field study in four governorates, using quantitative and qualitative methods to assess the accessibility and quality of FP services in family health units; the views of clients through in exit interviews; and the views of community members in focus group discussions with married women, husbands, and mothers-in-law on perception of FP, the quality of services, and service responsiveness to their needs. This study reconfirmed the need to focus on redressing staff turnover in rural primary health care (PHC) facilities, as well as improving the qualifications and skills of existing staff, both key constraints to quality improvement.